Optimizing crop management strategies for improved yield, water productivity, and sustainability of quinoa in shallow basaltic semi-arid regions - Pradhan, Aliza; Rane, Jagadish; Basavaraj, P. S.; Kumar, Neeraj; Shid, Dhanashri; Paul, Nobin C.; Pal, K. K.; Reddy, K. Sammi (Frontiers in Plant Science, 2025)
IntroductionRecently, quinoa (Chenopodium quinoa Willd.) has gained global recognition as a nutritious, adaptable crop suitable to adverse soil and climatic conditions. However, knowledge about optimal management practices for its cultivation in marginal areas of India is limited.MethodsIn this context, a field experiment was conducted in a split-split plot design with four sowing dates (D1: 1st November; D2: 15th November; D3: 1st December, D4: 15th December) in main plots, two irrigation levels (I1: 40% ETc; I2: 80% ETc) in sub-plots, and three nitrogen doses (N1: 100 kg N ha-1; N2: 150 kg N ha-1; N3: 200 kg N ha-1) in sub-sub plots having three replications during 2021-22 and 2022-23 in shallow basaltic murram soils.Results and discussionResults indicated that sowing on 1st November yielded the highest seed production of 1446 kg ha-1, as temperatures aligned closely with optimal growth conditions. Quinoa's drought tolerance meant that deficit irrigation was able to maintain the crop growth and yield. While the crop responded positively to higher N doses, the study found that applying 100 kg N ha-1 was optimal, considering shallow basaltic soil conditions and potential lodging issues. Additionally, water productivity, protein, and saponin content reflected similar trends to seed yield. The results suggested that early sowing, irrigation at 40% ETc, and 100 kg N ha-1 produced a seed yield of 1446 kg ha-1, demonstrating higher carbon efficiency and sustainability while minimizing N2O emissions. However, these strategies should be tailored to specific agro-ecological conditions. Overall, the findings confirm quinoa’s potential for cultivation in India’s 26 million hectares of shallow basaltic murram soils, where other crops may not thrive economically.